Rahman Shaari’s Insights in Improving the Political Reality of Malaysia: A Realism Analysis - Mary Fatimah, Subet; Asyraff, Jamin (Universiti Kebangsaan Malaysia Press, 2025)
Literary works have long played a significant role in reflecting and critiquing the political realities of societies worldwide. This intricate relationship between literature and politics reveals critical insights into power structures, societal dynamics, and political ideologies that shape nations. Therefore, this study explores how literature can contribute to improving the political realities of the nations. This is a qualitative study. Content analysis is based on Lukács’ theory of realism in his four renowned works (1963, 1978, 1989, 1990), focusing on the works of Malaysia’s National Laureate, Rahman Shaari, Pernikahan di Lubuk Hantu (2008), Semoga Molek (2012), and Cengkaman Hasrat (2015). The findings reveal that Rahman Shaari, as a realist writer, places significant emphasis on critiquing and addressing the negative aspects of political activities that harm society while offering constructive recommendations for creating a stable, democratic, and humanistic political reality. His insights on leaders’ inefficiency, the belittlement of women, negative political trends involving incitements, and the importance of selecting leaders wisely underscore his commitment to improving Malaysia's political reality. These novels exemplify the dual approach of critique and recommendation characteristic of realist literature, as emphasized by Lukács (1963, 1978, 1989, 1990). Rahman Shaari’s contributions provide valuable critiques and foster meaningful guidance for improving Malaysia’s political landscape. This study concludes that his literary works significantly benefit societal life and positively shape Malaysia’s political reality.